Integral mean of Green’s potentials and their conjugate - Vasyl'kiv, Ya. V.; Kravec, M. Ya. (Karpatsʹkì Matematičnì Publìkacìï, 2013)
The best possible estimates for Lebesgue integral means $m_q(r,F); (1le q <+infty)$ for the pair of functions $F= g+i:reveg$, here $g$ --- Green's potential, $reveg$ --- function conjugate to $g$, was obtained. It generalizes well-known results of Ya.V. Vasyl'kiv and A.A. Kondratyuk for logarithms $log; B$ of Blaschke products $B$ in terms of counting function $n(r,0,B)$; $(0<r<1)$ of their zeroes.